Vibration of the Metal Foam Sandwich Plates With FG-CNTRC Face Sheets via Isogeometric Analysis: Published online: 10/11/2025 - Pham, Duy-Khang; Huynh, Minh-Tan; Pham, Tan-Hung (Journal of Technical Education Science, 2025)
The objective of this paper is to investigate the free vibration behavior of sandwich plates composed of a metal foam core and two face sheets made of carbon nanotube-reinforced composite (CNTRC) materials. To achieve this, Reddy’s higher-order shear deformation theory (HSDT) combined with the isogeometric approach (IGA) is employed to develop the numerical model. The equations of motion are systematically derived using Hamilton’s principle, ensuring an accurate representation of both displacement and stress fields through the plate thickness. The proposed formulation is validated by comparing the present numerical results with available solutions reported in the existing literature, demonstrating excellent agreement. A comprehensive parametric study is conducted to assess the effects of key factors such as porosity distribution, CNT volume fraction, CNT distribution pattern, boundary conditions, and geometrical parameters on the natural frequencies of sandwich plates. The findings provide valuable insights for the optimal design and performance evaluation of advanced lightweight structural components with customized mechanical properties for aerospace, mechanical, and civil engineering applications.